Pengetahuan Kecacingan Menggunakan Media Video Pada Siswa Sekolah Dasar - Sahariyani, Menik; Sari, Rita Kartika; Tasyahuri, Syabila Aldiffah (Fakultas Kedokteran, Universitas Palangka Raya, 2024)
Helminthiasis in children still occurs in Seren Rembang. Educational video can enhance knowledge and attitudes in order to reduce the morbidity of Helminthiasis. This study aims to determine the impact of providing Helminthiasis educational video on the level of knowledge and attitude of students at SDN Seren Rembang. Research method is Quasi Experimental using a